The orbital tumors – some problems in diagnostics and treatment - Osmola, Krzysztof; Nowaczyk, Marian (Contemporary Oncology/Współczesna Onkologia, 2006)
A particularly unfavorable localization of a malignant tumor for the patient is the localization in vicinity of the orbital cavity. Besides the oncological problems, some other disturbances like ophthalmological concerned with eyeball and its muscles, neurosurgical concerned with the nearness to the central nervous system and problems with reconstruction and prosthesis of lost tissues may appear. None of the malignant tumors has predilection to this orbital area. In the literature epithelial tumors are most commonly described. The possibilities of the proper size of the biopsy for the purpose of histology diagnostics are also restricted and depend on the complicated anatomy and psychosocial functions of the face. Application of radiation therapy is also limited while epithelial tumors of the head and neck only in a small percentage tend to respond to chemotherapy. That is why surgical excision of the tumor with a proper margin of the uninvolved tissue is the basis of the treatment. This paper shows case reports of the patients with malignant tumors in the vicinity of the orbital area. Problems concerned with the management and treatment of such tumors are discussed below. Analysis of the difficulties in management and surgery intervention reveals necessity of close cooperation of different specialties.